Consumer behavior on the organic fruit and vegetable market: The evidence from Poland - Joanna Pawlak; Wioletta Wróblewska (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2022)
Consumer opinion and behavior research plays an important role in the development of the market of specific products. Currently, research in the field of consumer behavior towards organic food, which is gaining popularity on the Polish market whose production is in line with the concept of sustainable development and the European Green Deal related to it, is of particular importance. The aim of the study was to analyze the opinion and behaviors of consumers as regards organic fruit and vegetables and the promotion of these products as a determinant of them. The data for the analyzes came from empirical research conducted in Lublin at the turn of 2019 and 2020 by means of a proprietary questionnaire. The research was carried out on a sample of 534 respondents aged over 18. The scope of the research covered the opinions and behaviors of consumers towards organic fruit and vegetables as well as the factors determining the commencement of making or increasing the frequency of purchases of these products. An attempt was also made to define the relationship between the opinions and behaviors presented by consumers and their demographic and socio-economic characteristics. The results of the research show that half of the respondents purchased organic fruit and vegetables, of which only 1/4 claimed to do so regularly and quite often (several times a week). The respondents most often purchased these products in specialized stores - with organic food. According to the surveyed consumers, organic fruit and vegetables are rich in nutrients, healthy and safe, and produced using environmentally friendly methods. The most important factors influencing the increase in purchases and consumption and thus the development of the market for organic products were the increase in the availability of this product category in the places of everyday shopping and the reduction of their prices as the most important factors. The conducted research showed that for the respondents, promotional campaigns aimed at popularizing organic food, its values and impact on human health are not without significance.
Keywords: Q1; Q13; Q18; 650; consumer behavior; organic fruit and vegetables; promotion; organic farming